Understanding the Aircraft Mass Growth and Reduction Factor - Dieter Scholz (2020)
Purpose – This project work shows a literature survey, clearly defines the mass growth factor, shows a mass growth iteration, and derives an equation for a direct calculation of the factor (without iteration). Definite values of the factor seem to be missing in literature. To change this, mass growth factors are being calculated for as many of the prominent passenger aircraft as to cover 90% of the passenger aircraft flying today. The dependence of the mass growth factor on requirements and technology is examined and the relation to Direct Operating Costs (DOC) is pointed out. --- Methodology – Calculations start from first principles. Publically available data is used to calculate a list of mass growth factors for many passenger aircraft. Using equations and the resulting relationships, new knowledge and dependencies are gained. --- Findings – The mass growth factor is larger for aircraft with larger operating empty mass ratio, smaller payload ratio, larger specific fuel consumption (SFC), and smaller glide ratio. The mass growth factor increases much with increasing range. The factor depends on an increase in the fixed mass, so this is the same for the payload and empty mass. The mass growth factor for subsonic passenger aircraft is on average 4.2, for narrow body aircraft 3.9 and for wide body aircraft (that tend to fly longer distance) 4.9. In contrast supersonic passenger aircraft show a factor of about 14. --- Practical implications – The mass growth factor has been revisited in order to fully embrace the concept of mass growth and may lead to a better general understanding of aircraft design. --- Social implications – A detailed discussion of aircraft costs as well as aircraft development requires detailed knowledge of the aircraft. By understanding the mass growth factor, consumers can have this discussion with industry at eye level. --- Originality/value – The derivation of the equation for the direct calculation of the mass growth factor and the determination of the factor using the method for 90% of current passenger aircraft was not shown.
Keywords: aviation; aircraft; passenger; mass; growth; payload; range; fuel; consumption; aerodynamics